1967
DOI: 10.1113/jphysiol.1967.sp008330
|View full text |Cite
|
Sign up to set email alerts
|

The relative sensitivity to vibration of muscle receptors of the cat

Abstract: SUMMARY1. Longitudinal vibration was applied to the de-efferented soleus muscle of anaesthetized cats while recording the discharge of single afferent fibres from the proprioceptors within the muscle. Conditions were defined under which vibration can be used to excite selectively the primary endings of muscle spindles without exciting the secondary endings of muscle spindles or Golgi tendon organs.2. Frequencies of vibration of 100-500 c/s were used. The maximum amplitude of vibration which the vibrator could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
258
5
2

Year Published

1971
1971
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 418 publications
(281 citation statements)
references
References 28 publications
(52 reference statements)
14
258
5
2
Order By: Relevance
“…In previous studies, muscle vibration has been associated with high activation of various skin and subcutaneous receptors; further, it has been reported that the la-afferent of the agonist muscle also cause a very high level of activity (Baik & Lim, 2006;Brown et al, 1967;Cordo et al, 1998;Roll & Vedel, 1982). In the study of Sabin (2003), it was confirmed that the lower extremity muscles were activated by vibratory stimulation during gait, which was attributed to vibration activating la-afferent of muscle spindle.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, muscle vibration has been associated with high activation of various skin and subcutaneous receptors; further, it has been reported that the la-afferent of the agonist muscle also cause a very high level of activity (Baik & Lim, 2006;Brown et al, 1967;Cordo et al, 1998;Roll & Vedel, 1982). In the study of Sabin (2003), it was confirmed that the lower extremity muscles were activated by vibratory stimulation during gait, which was attributed to vibration activating la-afferent of muscle spindle.…”
Section: Discussionmentioning
confidence: 99%
“…5. The size of the reflex tension from TVR-f relation depends on the discharge frequency of the unitary EMG, which occurs according to the principle of the integer multiplication of original vibratory cyclic time.It has been demonstrated in cat musclethat primary spindle endings are much more sensitive to muscle vibration than secondary endings, their maximal response frequency being around 400Hz (GRANIT and HENATSCH, 1956;BESSOU and LAPORT, 1962;BIANCONI and VAN DER MEULEN, 1963;BROWN et al, 1967). It has also been reported by several authors that group Ia afferent discharges elicited by sinusoidal stretch activate the spinal motoneuron monosynaptically (MATTHEWS, 1966;HOMMA et al, 1967).…”
mentioning
confidence: 93%
“…Neurons were considered to respond to activated muscle proprioceptors when they (1) were sensitive to sinusoidal muscle stretching (Lundberg and Winsbury, 1960;Bianconi and van der Meulen, 1963;Brown et al, 1967;Matthews and Stein, 1969;Stuart et al, 1970;Mackie et al, 1998), showing a tight phase locking at the tested frequencies of 130 -135 Hz (Mackie et al, 1998); (2) produced spike bursting during stretching, a rapid drop in discharge on completion of the dynamic phase of stretching, and then a relatively slow drop during the holding phase (Matthews, 1933;Harvey and Matthews, 1961;Matthews, 1981;Edin and Vallbo, 1990); and (3) showed silenced firing during muscle shortening (stretch release) (Matthews, 1981;Edin and Vallbo, 1990;Grill and Hallet, 1995). It became clear during the first successful experiments in three distinct animals that cells responding in a 1:1 fashion to 130 -135 Hz muscular sinusoidal vibration also responded to manual muscle stretch (by flexing or extending the appropriated articulation), showing bursting discharges during the dynamic phase of stretching followed by a fall in discharge rate during holding and silenced firing during shortening.…”
Section: Methodsmentioning
confidence: 99%